Urban Ecological Safety Evaluation Based on Fuzzy Matter-Element Theory - Tao Xiaoyan (Institute of Advanced Engineering and Science, 2014)
There are many tourism cities in China and sustainable development of urban tourism has become an important field of tourism research. An ecological safety evaluation index system of tourism city was constructed. The evaluation index system was composed of resource, environmental, economic and social subsystem. Then an evaluation model based on fuzzy matter-element theory was established. Finally a case study on Kaifeng city was developed. The results showed that there was a tendency of gradual improvement in ecological safety condition of Kaifeng city. However, ecological safety condition during the period belonged to critically safe grade. Therefore, ecological safety condition of Kaifeng was unsatisfactory. The study can provide scientific basis for decision-making of local governments and concerned departments, help people know the influences of tourism activities on ecological environment scientifically and timely, and help tourists advance ecological consciousness. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4659